The neuroanatomy of Zulmasuchus querejazus (Crocodylomorpha, Sebecidae) and its implications for the paleoecology of sebecosuchians. Issue 10 (26th November 2021) - Pochat‐Cottilloux, Yohan; Martin, Jeremy E.; Jouve, Stéphane; Perrichon, Gwendal; Adrien, Jérome; Salaviale, Céline; de Muizon, Christian; Cespedes, Ricardo; Amiot, Romain
Abstract: The endocranial structures of the sebecid crocodylomorph Zulmasuchus querejazus (MHNC 6672) from the Lower Paleocene of Bolivia are described in this article. Using computed tomography scanning, the cranial endocast, associated nerves and arteries, endosseous labyrinths, and cranial pneumatization are reconstructed and compared with those of extant and fossil crocodylomorphs, representative of different ecomorphological adaptations. Z. querejazus exhibits an unusual flexure of the brain, pericerebral spines, semicircular canals with a narrow diameter, as well as enlarged pharyngotympanic sinuses. First, those structures allow to estimate the alert head posture and hearing capabilities of Zulmasuchus . Then, functional comparisons are proposed between this purportedly terrestrial taxon, semi‐aquatic, and aquatic forms (extant crocodylians, thalattosuchians, and dyrosaurids). The narrow diameter of the semicircular canals but expanded morphology of the endosseous labyrinths and the enlarged pneumatization of the skull compared to other forms indeed tend to indicate a terrestrial lifestyle for Zulmasuchus . Our results highlight the need to gather new data, especially from altirostral forms in order to further our understanding of the evolution of endocranial structures in crocodylomorphs with different ecomorphological adaptations.